The Feasibility of Deferred Prosecution Agreements for Individual Corruption Offenders in Indonesia - Melta Variza; Sanusi Sanusi; Mohd Din; Yusri Yusri; Yusrizal Yusrizal (SCAD Independent, 2026)
Indonesia’s anti-corruption enforcement remains predominantly conviction-oriented, and the recovery of state financial losses has not been maximized. Article 4 of the Anti-Corruption Law requires prosecution to continue even after full restitution has been made, which limits prosecutorial flexibility and often results in enforcement costs that exceed the value of the losses in low-value corruption cases. This study examines the feasibility of applying Deferred Prosecution Agreements (DPA) to individual corruption offenders in Indonesia. Using normative juridical research with statutory and comparative approaches, the study analyzes Indonesian legal provisions alongside DPA practices in the United Kingdom and the United States. The findings reveal that Indonesia’s current legal framework lacks a mechanism for the conditional termination of prosecution following restitution, although the prosecutorial role as dominus litis offers an institutional basis for such reform. Comparative analysis shows that a DPA combines restitution, cooperation, judicial oversight, and prosecutorial discretion within a structured legal mechanism. Consequently, this study proposes a normative-operational DPA model for individual offenders involving state financial losses below IDR 200,000,000, subject to full restitution, administrative sanctions, judicial approval, and compliance monitoring. Ultimately, this study contributes a legally feasible framework for reorienting anti-corruption prosecution away from incarceration-centered punishment toward more efficient and accountable state asset recovery.